Adaptation of Tyler's Evaluation Model in Assessing the Success of Project-Based Learning in the Implementation of the Independent Curriculum at SMP Patriot Bekasi - Mawaddah Warohmah; Rida Ayu Agustin; Syafiyah Nur’ani Rahmah (CV Kalimasada Group, 2025)
This study aims to evaluate the effectiveness of implementing the Tyler evaluation model in assessing project-based learning within the framework of the Independent Curriculum at SMP Patriot Bekasi. The Independent Curriculum promotes a shift in learning paradigms, one of which is through project-based learning that emphasizes the holistic development of students’ character and competencies. A descriptive qualitative approach was employed, using data collection techniques including interviews, observations, and documentation. Interviews were conducted with school principals, teachers, students, and parents; observations focused on the learning process, infrastructure, and curriculum implementation support; while documentation provided supplementary data related to learning programs. The findings indicate that the adaptation of Tyler’s evaluation model—which focuses on alignment between learning objectives, experiences, and outcome assessments—effectively enhanced student motivation, creativity, and critical thinking. The learning process became more engaging and meaningful. The synergy between teachers, students, schools, and parents emerged as a key factor in the successful implementation of the projects. The evaluation encompassed cognitive, affective, and psychomotor domains, contributing to the realization of the Pancasila Student Profile values. However, the study also identified several challenges, including limited teacher familiarity with new methodologies, inadequate facilities, and varying levels of student readiness for project-based learning. These findings suggest that while Tyler’s model can be effectively adapted to support the Independent Curriculum, its success depends on continued professional development for teachers and improved learning infrastructure.